The Africa non-communicable diseases (NCD) Open Lab: Impact of a portfolio of clinical studies to deepen the understanding of NCDs in sub-Saharan Africa - Addo, Juliet; Davy, Maria; Newlands, Amy; Orford, Lindsay; Guta, Phyllis; Scott, Rhona; van Hasselt, James; Maher-Edwards, Gareth (International Society of Global Health, 2024)
Clinical research in sub-Saharan Africa (SSA) has often focussed on communicable diseases. However, with the increasing burden of non-communicable diseases (NCDs), there is a need for Africa-specific NCD research. GSK established the Africa NCD Open Lab in 2014. Three calls for proposals were advertised through various media channels. An external independent scientific advisory board, predominantly representing African scientists and NCD experts, reviewed and selected projects to receive funding. An additional programme in the Africa NCD Open Lab was designed to build statistical capability by supporting training initiatives. We assessed the impact of the Africa NCD Open Lab in three ways: scientific quality with impact; research training and professional development; and research environments. We captured metrics through regular reports/interactions with researchers; via a final report; and through exit interviews with principal investigators. Twenty projects in 11 African countries were funded; reports from 18 completed projects are available (data capture is ongoing). Overall, 139 articles have been published in peer-reviewed journals and other data have been presented at conferences and other forums. Most completed projects led to positive outcomes, such as further research, informing policy, or positively impacting clinical care, including three projects that saw changes to regional or national practice guidelines: the CREOLE study in Nigeria; the African Severe Asthma Program in Uganda; and the African Prospective Study on the Early Detection and Identification of Cardiovascular Disease and Hypertension in South Africa. Participation in the Africa NCD Open Lab led to the award of 34 grants related to or influenced by increased research capacity or experience. Significant professional development related to the projects also occurred with higher-level degrees being awarded, including 30 MScs, 30 PhDs, and nine postdoctoral fellowships. Through these projects, research capacity was strengthened across the region by equipping core research facilities, training research staff, strengthening research support services, and supporting the expansion of investigator networks. The completed Africa NCD Open Lab projects demonstrate high-quality research outcomes addressing important health challenges with potential benefits to African populations. Based on the success of the Africa NCD Open Lab, additional funding has been secured to extend the Open Lab initiative.
Keywords: Clinical research in sub-Saharan Africa ; Africa non-communicable diseases ; Open Lab; understanding of NCDs in sub-Saharan Africaclinical studies